2017
DOI: 10.2147/ijwh.s119724
|View full text |Cite
|
Sign up to set email alerts
|

Self-management and psychological-sexological interventions in patients with endometriosis: strategies, outcomes, and integration into clinical care

Abstract: Endometriosis has a multifactorial etiology. The onset and progression of the disease are believed to be related to different pathogenic mechanisms. Among them, the environment and lifestyle may play significant roles. Diet, dietary supplements, physical exercise, osteopathy, massage, acupuncture, transcutaneous electrical nerve stimulation, and Chinese herbal medicine may represent a complementary and feasible approach in the treatment of symptoms related to the disease. In this narrative review, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 110 publications
0
53
0
3
Order By: Relevance
“…Recently, Buggio et al . described interventions for the self‐management of physical, psychologic, and sexual symptoms for women with endometriosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Buggio et al . described interventions for the self‐management of physical, psychologic, and sexual symptoms for women with endometriosis .…”
Section: Discussionmentioning
confidence: 99%
“…The other review evaluated physical exercise among women with endometriosis, but it included studies that were not randomized controlled trials (RCTs) and found that data were inconclusive on the benefits of exercise for improving pain symptoms. Buggio et al . present a view on psychologic and sexual aspects related to endometriosis, discussing several points leading to the self‐management of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Manejo terapéutico En el caso de la endometriosis, el tratamiento más utilizado para mejorar sus síntomas es el hormonal. Sin embargo, se ha sugerido la utilización de medicina china basada en plantas, y medicina alternativa; así como apoyo psicológico y de sexología para abarcar de manera integral la sintomatología presentada por las mujeres que padecen la patología (26). Al respecto Zhao et al (27) investigaron el impacto de la relajación muscular progresiva sobre los niveles de ansiedad, Depresión y calidad de vida de los pacientes con endometriosis Sometidos a terapia de agonistas de GnRH.…”
Section: Respuesta Emocional Y Desordenes Psiquiátricosunclassified
“…41,42 Complementary and alternative medicine (CAM) has been used extensively in most Asian countries since the nineteenth century; however, their utilization in Western countries has been rapidly growing. 43,44 As stated by the World Health Organization, CAM comprises a range of different health-related strategies that can be defined as predominantly operating outside the conventional medical curriculum and profession. 45 The list of CAMs includes several procedures and products that have been tested in the treatment of women with endometriosis, such as osteopathic manipulative therapy (OMT), massages, acupuncture, transcutaneous electrical nerve stimulation (TENS), CHM, vitamins, and dietary supplementations.…”
Section: Other Medicationmentioning
confidence: 99%
“…However, no definitive conclusions can be drawn from these studies, due to the small sample sizes. 44 TENS is a non-invasive and low-cost technique based on the use of mild electrical impulses applied to the intact surface of the skin with the objective of stimulating lowthreshold nerves to relieve pain and favor the release of endogenous opioids. TENS has been mentioned as alternative short-term pain management in women with dysmenorrhea in a consensus document on the management of endometriosis.…”
Section: Acupuncture and Tensmentioning
confidence: 99%